THE CORPORAL ICONOTROPISM OF VASYL STEFANYK - Soletskyi, Oleksandr (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2022)
Aim. The paper deals with the mutual transition of visual experience into verbal one in acts of creativity evidenced from the poetics of bodily iconotropism by Vasyl Stefanyk. The author focuses on identifying and interpreting the writer’s texts as the ‘body’ of the author, relying on Stefanyk’s self-reflexions and self-commentaries about his creative modes. The purpose of the paper is to establish the functionality and expressiveness of ‘corporeality’ as a semiotic and metaphysical phenomenon. Methods. The study follows a system of genetic, hermeneutic, and semiotic methods. The author draws on the scientific methodology of semiotics and hermeneutics, applies the cognitive theory of literature (cognitive poetics) tenets and research methodology of the psychology of artistic creativity. This is due to the distinctive nature of the study, its subject of inquiry and scope of research. Results. The paper reviews the history of the corporeality poetics in fiction, noting its versatility and meaning-making focus, cultural and cognitive effects. Based on the studies of Stefanyk’s texts and epistolary, the main iconotropic qualities of ‘corporeality’ and their contribution to the formation of dominant images and meaning-oriented codes have been noted. Originality. The paper is the first attempt for summarizing observations on the phenomena of corporeal iconotropism in the works of Vasyl Stefanyk and ascertaining their multilevel functionality for artistic modelling. Practical significance. The paper provides a platform for further inquiry into the phenomena of corporeal iconotropism, the poetics of corporeality in fiction in general, and the work of Vasyl Stefanyk in particular. The findings can underpin coursework and graduation theses.